First Prize, Public Sculpture for the Conference Centre in Nicosia to be used for the Cyprus Presidency of the European Union - Antoniou, Klitsa (My University, 2026)
First Prize, Public Sculpture for the Conference Centre in Nicosia to be used for the Cyprus Presidency of the European Union. The proposal was selected among 85 proposals. The work has been realized and exhibited permanently at the entrance of the Conference Room of the above building.
Keywords: Arts and entertainment